RODENT SPECIES AND STRAIN DIFFERENCE IN KIDNEY AND LUNG PATHOLOGY INDUCED BY N-ETHYL-N-HYDROXYETHYLNITROSAMINE - Nakaoka, Shingo; Matsuda, Hirofumi; Ohshima, Masato; Kitahori, Yoshiteru; Kitamura, Motokazu; Tsuzuki, Toshihide; Hiasa, Yoshio; Konishi, Noboru; Hayashi, Isao (Journal of Toxicologic Pathology, 1994)
Lung and kidney tumor induction was evaluated in hamsters and in 2 strains each of rats and mice given N-ethyl-N-hydroxyethylnitrosamine (EHEN) for 2 weeks in either the drinking water or mixed in the diet. Both male and female Wistar rats developed renal cell tumors, while hyperplastic tubules were the characteristic lesions observed in the kidneys of male F344 rats, male BALB/c, and A/J mice, and male Syrian golden hamsters. In contrast, lung adenomas and carcinomas were induced in both strains of mice but not in rats or hamsters. It thus appears that there are differences in susceptibilities between strains as well as between species in EHEN carcinogenicity.